The Structure and Composition of Gainesville's Urban Forest in 2016 - Michael G. Andreu; Caroline A. Hament; David A. Fox; Robert J. Northrop (EDIS)
Trees in cities were formerly thought of merely as a collection of individuals found along streets and incorporated into landscaping. However, urban trees are now viewed as being part of a unique forest type, and understanding the urban forest’s structure and composition is an important first step towards managing it. This 4-page fact sheet written by Michael G. Andreu, Caroline A. Hament, David A. Fox, and Robert J. Northrop and published by the UF/IFAS School of Forest Resources and Conservation aims to provide a broader understanding of the urban forest in the city of Gainesville, Florida. http://edis.ifas.ufl.edu/fr413